2010
DOI: 10.2217/rme.09.83
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Angiogenesis by Transplantation of Human Embryonic Stem Cell-Derived CD133 + Endothelial Progenitor Cells for Cardiac Repair

Abstract: hESC-derived CD133(+) endothelial progenitor cells can be utilized to regenerate the infarcted heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…EPCs or CD34 positive/CD133 positive cells have been demonstrated to repair the denuded vessel walls and to promote renewal of endothelium (Rufaihah et al, 2010;Senegaglia et al, 2010;Walter et al, 2002). CD34 positive cells play an indispensable role in angiogenesis (Al-Jarrah et al, 2010;Stellos et al, 2010;Wang et al, 2010).…”
mentioning
confidence: 99%
“…EPCs or CD34 positive/CD133 positive cells have been demonstrated to repair the denuded vessel walls and to promote renewal of endothelium (Rufaihah et al, 2010;Senegaglia et al, 2010;Walter et al, 2002). CD34 positive cells play an indispensable role in angiogenesis (Al-Jarrah et al, 2010;Stellos et al, 2010;Wang et al, 2010).…”
mentioning
confidence: 99%
“…Additionally, replenishing the lack of EPCs in TAO patients has a more direct mode of action and can be used for the prevention as well as the treatment of TAO. Several studies have suggested the use of EPCs for therapeutic purposes in other diseases, [36][37][38] and the results were promising. Since studies of EPC injection in TAO have not been performed yet, this could be another possible target for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several diverse cell types have been derived from hESCs, including cardiomyocytes [66,67], endothelial cells [68][69][70], chondrocytes [71][72][73][74][75], osteoblasts [76][77][78], neurons [79][80][81], keratinocytes [82,83], and hepatocytes [84].…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%